Laptop Cooling Pad Temperature Monitoring System - Shamsul Kamal Ahmad Khalid; Noor Azah Samsudin; Nor Amirul Amri Nordin; Muhammad Syariff Aripin (Institute of Advanced Engineering and Science, 2018)
Cooling pads are commonly used to reduce temperature of laptop to avoid overheating problem. However, existing cooling pads are prone to various limitations: fixed voltage in the hardware component, inaccurate temperature readings and lacked of computer-based temperature monitoring functions. In this paper, a laptop cooling system with multivoltage fan speed controller using real-time processor temperature readings is proposed. A graphical user interface (GUI) and color coded LEDs are also implemented to provide visual inspection of the temperature values captured from the laptop. The temperature values are displayed in graph and tabular form. The performance of the proposed cooling pad with computer-based monitoring application is evaluated against two other types of existing cooling pad systems. The experiments have shown that the temperature values can be monitored clearly with the proposed GUI. More importantly, the proposed cooling pad system has the potential to achieve lower temperature faster than the rest of the existing cooling pad systems.